Management of Cardiovascular Diseases in Chronic Hemodialysis Patients - Zhen Zhang; Yaqiong Wang (Reviews in Cardiovascular Medicine, 2023)
Hemodialysis (HD) is the main treatment modality for patients with end-stage kidney disease. Cardiovascular diseases (CVD) are highly prevalent in HD patients and are the leading cause of death in this population, with the mortality from CVD approximately 20 times higher than that of the general population. Traditional and non-traditional cardiovascular risk factors accelerate progression of CVD and exacerbate the prognosis in HD patients. This review provides a brief overview of the characteristics of CVD in HD patients, and a description of advances in its management.